(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In 2001, The Common European Framework of Reference for Languages (CEFR) laid the groundwork for the development of language proficiency, thereby emphasizing the skills of students in education and professional development. ESOL and CEFR tests and normative documents are used by Cambridge University in many countries of the world to improve and develop this to meet the high quality of education.